Enhancing agro-tourism through travel inspiration and hedonic motivation on visit intention - Sa'adah, Siti Lailatus; Maulidah, Silvana; Asmara, Rosihan; Rahman, M Shadiqur (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
The proliferation of short-form videos, especially on platforms like TikTok, has become a powerful tourism marketing tool, influencing travelers' decisions and intentions. This study examines how the characteristics of these videos affect visit intentions, with travel inspiration and hedonic motivation as mediators, and openness to experience as a moderator. Using convenience sampling, 174 active TikTok users were surveyed and analyzed through partial least squares. The results show that short-form videos significantly influence travel inspiration, which in turn positively impacts hedonic motivation and travel intention. Travel inspiration also mediates the effect of short-form videos on both hedonic motivation and travel intention. Furthermore, openness to experience enhances the relationship between short-form videos and travel intention. All eight hypotheses tested were found to have a positive and significant effect, indicating that short-form videos effectively shape travel decisions through various motivational factors.